Is it Really a Universal Phenomenon? - Preferential Attachment in Alliance Networks - Oliver Rossmannek; Olaf N. Rank (European Management Review, 2020)
We study preferential attachment (i.e., a rich-get-richer effect) in alliance networks. Thereby, we argue that various levels (firm, firm group, country) influence the strength of preferential attachment. To test our hypotheses, we take a sample of 117 airlines from 74 countries in the period 2001 to 2011. For the estimation, we use stochastic actor-oriented models, a method for analyzing longitudinal network data. As a result, we find that preferential attachment is stronger for firms that have fewer resources and are located in a less-developed country. Consequently, we show how different competitive positions affect alliance strategies.
Keywords: 650; strategic alliances; airline industry; network analysis; preferential attachment; network evolution; stochastic actor-oriented models